Risk factors of carbapenem-resistant gram-negative bacteria pneumonia and mortality: Carbapenem-resistant gram-negative bacteria pneumonia - Wenwen, Shen; Xiquan, Liang; Aiqin, Lin (Cellular and Molecular Biology, 2022)
This experiment aimed to study the risk factors of carbapenem-resistant Gram-negative bacteria pneumonia and death. For this aim, a total of 181 patients with Gram-negative bacterial pneumonia treated from March 2020 to March 2022 were retrospectively selected and divided into the drug-resistance group (n = 96) and the non-drug resistance group (n = 85) according to the carbapenem resistance. According to the prognosis, the drug resistance group was divided into the survival group (n = 82) and the non-survival group (n = 14), respectively. The risk factors of single and multi-factor carbapenem-resistant Gram-negative bacteria pneumonia and death were studied. Results showed that univariate analysis showed that the rates of recent surgery, respiratory failure, shock, indwelling catheterization and disturbance of consciousness were significantly higher in the drug-resistant group than in the non-drug-resistant group. The univariate analysis also showed that the rates of coronary heart disease, diabetes, shock, renal insufficiency, deep venous catheterization and respiratory failure were significantly higher in the non-survival group than in the survival group. Multivariate analysis showed an increased risk of carbapenem-resistant gram-negative pneumonia in patients who had used carbapenem-resistant antibiotics, hypertension, coronary heart disease, and malignancy in the previous 90 days. Patients with carbapenem-resistant gram-negative pneumonia who had coronary heart disease, diabetes mellitus, shock, renal insufficiency, deep venous catheterization, and respiratory failure were at increased risk of death. In conclusion, recent surgery, respiratory failure, shock, indwelling catheterization, and disturbance of consciousness are risk factors for carbapenem-resistant Gram-negative bacteria pneumonia. Coronary heart disease, diabetes mellitus, shock, renal insufficiency, deep venous catheterization and respiratory failure are risk factors for death from carbapenem-resistant gram-negative bacteria pneumonia.